Electrochemical Corrosion Behavior and Microstructural Characterization of HVOF Sprayed Inconel-718 Coating on Gray Cast Iron - Vasudev, Hitesh; Prashar, Gaurav; Thakur, Lalit; Bansal, Amit (Journal of failure analysis and prevention, 2021)
In the present work, Inconel-718 (IN718) coating was developed on a gray cast iron (C.I) substrate by utilizing a high-velocity oxy-fuel spray technique. The microstructural analysis was performed to know the topological characteristics of the deposited IN718 coating. Corrosion testing of bare and coated samples was carried out at an ambient temperature in a NaCl solution (3.5 wt.%) using potentiodynamic polarization technique. The kinetics of corrosion and surface characteristics of the as-sprayed and corroded coatings were studied by scanning electron microscopy/energy-dispersive spectroscopy techniques. The different phases in the feedstock powder and as-sprayed coating were determined through X-ray diffraction analysis. The reported average microhardness value of the developed IN718 coating was 563 ± 15 HV0.2. The increased hardness of the IN718 coating is credited to the existence of Mo and Ti elements in the IN718 coatings. Corrosion testing showed that the IN718 coating exhibited the maximum corrosion resistance compared to a C.I. substrate due to a stable passive layer in the IN718 specimen.Graphic Abstract